Evaluation of thermodynamic data and phase equilibria in the system Ca-Cr-Cu-Fe-Mg-Mn-S Part II: Ternary and quasi-ternary subsystems. (March 2017) - Jantzen, Tatjana; Hack, Klaus; Yazhenskikh, Elena; Müller, Michael
Abstract: The Ca-Cr-Cu-Fe-Mg-Mn-S system has been thermodynamically assessed using all available experimental data. Sulfur is introduced into the thermodynamic description of 8 solid solution phases such as Thiospinel, Digenite, Oldhamite, Cu2 S-I, Cu2 S-II, Pyrrhotite, Brezinaite, Chalcopyrite-HT using available experimental information. Particular attention was given to the phase Pyrrhotite which forms at high temperatures a solid solution with end-members Fe1−x S and Cr1−x S in the ternary Cr-Fe-S system, and also the phase Digenite, which exhibits very wide solubility toward Pyrrhotite in the Cu-Fe-S system. In this part of the report ternary and quasi-ternary subsystems are presented while all relevant binary systems as well as pseudo-binary sections have already been presented in Part I of this series. Highlights: Ca-Cr-Cu-Fe-Mg-Mn-S system thermodynamically assessed. Ternary Me1 -Me2 -S and quasi-ternary systems Me1 S-Me2 S-Me3 S considered here. Modified associate species model used for the liquid phase. 8 solid solutions introduced using the multi-sublattice approach. Calculated phase diagrams and thermodynamic properties in good agreement with the experimental data.